Intergenerational Mobility and Subjective Well-Being - Ghanghro, Ali akbar (Université d'Ottawa | University of Ottawa, 2009)
Using information on 45,000 individuals from 20 OECD countries from the World Values Survey, this paper analyzes the relationship between Subjective Well-Being and the intergenerational transmission of inequality as measured by intergenerational earnings